T Tinjauan Naratif: Peran Fungsi Interprofessional Education (IPE) dan implementasi Interprofessional Collaboration (IPC) dalam Pendidikan Kesehatan melalui perspektif Keperawatan Kritis - Eirene Eunike Meidiana Gaghauna (LPPM Universitas Sari Mulia, 2021)
BACKGROUND Health provider are profesional staff who has wide competencies and services in order to maintaining and increasing the quality of health service based on patient centered care. OBJECTIVE The purpose of this study was to describe the function and role of Interprofesional Education and Interprofesional Collaboration thrcough Critical Care Nursing Perspective METHODS Non-systematic review literature study method has been applied.The author hans been used scientific article from several database including Science Direct, BMJ, Google Scholar and Reflevtive Journal. . CONCLUSION The implementation of Interprofesional Education and Interprofesional Collaboration are very important as provisions to the student as a leader in the future